Uncovering Potential Therapeutic Targets for Spinal Cord Injury; Insights from Single-Cell and Cross-Species Transcriptomics - Abouzekry, Sara Samy (AUC Knowledge Fountain, 2026)
Central nervous system (CNS) injury remains a devastating healthcare problem. Despite years of research, it remains almost impossible to achieve meaningful functional repair following traumatic brain injury (TBI) and spinal cord injury (SCI). Spinal cord injury (SCI), a highly devastating subset of CNS trauma, is considered a challenge due to the extremely limited regenerative capacity of the nervous system in adult mammals. In contrast, certain species display remarkable repair abilities followed by moderate regenerative ability in neonatal mammals, indicating that regeneration is shaped by the evolutionary context as well as the developmental age. To uncover the core molecular mediators of regeneration, we integrated a systematic review of single-cell RNA-seq (scRNA-seq) studies of CNS injury and a cross-species meta-analysis of differential gene-expression studies post-SCI. First, we reviewed scRNA-seq studies across CNS injuries to explore cell-type–specific molecular events that follow injury, including SCI and TBI. These analyses revealed shared enrichment of cell-cycle processes, immune system response, and extracellular matrix (ECM) remodelling. Each exhibits a controlled temporal and cell-specific regulation. Regenerative capacity appeared to be restricted to limited cell populations, such as subventricular zone progenitors and a subset of neurons expressing regeneration-associated genes (RAG). Moreover, neonatal microglia have been shown to adopt a pro-regenerative state that enables scar-free repair. This feature is absent in adults. We suggest that these promising yet limited responses represent therapeutic windows that need further exploration. Our results suggest that failure of regeneration in poorly regenerating systems overwhelms the limited cellular populations that are capable of repair. We then conducted a systematic review of 167 genome-wide SCI studies; 42 were selected, spanning bulk RNA-seq, microarray, scRNA-seq, and single-nucleus RNA-seq platforms. Meta-analysis of 9 eligible cross-species studies revealed 824 differentially expressed genes (DEG) shared between spinal cord-regenerating (REG group; lamprey, zebrafish, axolotl, tadpole) models and non-spinal cord-regenerating (Non REG group; adult rat and adult mouse) models. Protein–protein interaction (PPI) analysis was conducted on the oppositely regulated DEG shared between the REG and Non-REG groups. Notably, the hub genes identified in this analysis (CCNA2, CCNB1, CCNB2, CDC20, MCM4, PLK1, MAD2L1, RRM2, KIF23, and FBXO5) were upregulated in the non-regenerating adult mouse during the first week post-SCI. Moreover, they were predominantly associated with cell cycle and mitotic activation. This is consistent with the previous hypothesis, suggesting that aberrant proliferation through overactivated cell cycle response contributes to glial scarring and worsened repair outcomes. Together, these findings support a unified theme: regeneration is based on time-dependent, cell-type–specific responses, as observed in neonatal microglia and specific progenitor cell populations. Adult mammalian SCI is shown to exhibit excessive activation of cell-cycle and proliferative pathways that may worsen glial scarring. In addition, regeneration fails when cell-cycle and immune responses become dysregulated, thereby exceeding the capacity of the small, limited populations capable of true repair. By integrating single-cell insights with cross-species transcriptomic gene-expression meta-analysis, our work highlights conserved molecular signatures and responses that distinguish regenerative from non-regenerative systems and lays a foundation for future studies comparing injury responses across age groups to reveal transcriptional programs that underlie high versus low regenerative potential.